2011
DOI: 10.1016/j.jbusres.2010.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation, management commitment, and human capital: The internationalization of SMEs in India

Abstract: a b s t r a c tSmall-and medium-sized enterprises (SMEs) make sizeable contributions to the economic success of nations. Research concerning the internationalization of SMEs is available in the context of developed economies but less is can be found dealing specifically with the entrepreneurial behavior and international expansion of SMEs in emerging markets such as India. This research extends the literature addressing the relationships surrounding the internationalization of SMEs in India as related to entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
280
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(295 citation statements)
references
References 82 publications
10
280
0
5
Order By: Relevance
“…Extant studies often point to how di↵erent orientations of a firm, such as the entrepreneurial orientation, international market orientation or 49 2. THEORETICAL FRAME growth orientation, impact its internationalization (Javalgi and Todd, 2011;Ruokonen, 2007;Knight and Kim, 2009). These di↵erent orientations directly a↵ect knowledge acquisition and information interpretation within an organization (Dasí et al, 2015).…”
Section: Input and Influence From The Organizational Levelmentioning
confidence: 99%
“…Extant studies often point to how di↵erent orientations of a firm, such as the entrepreneurial orientation, international market orientation or 49 2. THEORETICAL FRAME growth orientation, impact its internationalization (Javalgi and Todd, 2011;Ruokonen, 2007;Knight and Kim, 2009). These di↵erent orientations directly a↵ect knowledge acquisition and information interpretation within an organization (Dasí et al, 2015).…”
Section: Input and Influence From The Organizational Levelmentioning
confidence: 99%
“…The previous researches on the industry of different countries indicate that active companies in the industry sector of each country play important roles in national and economical development of these countries (Javalgi et al, 2011). Entrepreneurship identifies not only the technological inefficiency but also the inefficiency of the time and place in an economy (Shane & Venkataraman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…International scale (sometimes called international intensity or international degree) and international scope are the common dimensions of international performance (Autio et al, 2000;Frishammar & Andersson, 2008;Javalgi & Todd, 2011;Ripolles et al, 2007;Robertson & Chetty, 2000;Sullivan, 1994;Zahra & George, 2002;Zahra et al, 1997;Zhang et al, 2012). In a review study of international performance, Walters and Samiee (1990) demonstrated that 68% of reviewed papers implemented international scale and 13% employed international scope to measure international performance.…”
Section: Research Variables and Measurementsmentioning
confidence: 99%
“…Even though this may reduce the generalizability of the results, it is needed to achieve valid and reliable conclusions. Firm size (Balabanis & Katsikea, 2003;Dhanaraj & Beamish, 2003;Francis & Collins-Dodd, 2000) and previous international experience (Axelsson & Agndal, 2000;Javalgi & Todd, 2011;Kuivalainen et al, 2007;Lan & Wu, 2010;Reuber & Fischer, 1997) are also represented as factors that may influence the decision and subsequent activities of internationalization. Thus, they are usually controlled in internationalization research (e.g.…”
Section: Research Variables and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation